1959
DOI: 10.3181/00379727-101-24960
|View full text |Cite
|
Sign up to set email alerts
|

Pathway of Enterogastric Reflex.

Abstract: 407system was present in both fascicular and reticular zones. The comparatively low concentrations in the glomerulosa were due a t least in part to1 a relative lack of specific dehydrogenase activity. One can not rule out by this method the possibility that TPN may also be low in the glomerulosa, because T P N is added in reaction I. If as has been suggested one of the roles played by this enzyme system in the cortex is to act as a TPNH generator, providing this reductant for important hydroxylations of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1962
1962
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The reflexes can be elicited by distension of the colon and by distension or chemical stimuli applied intraluminally in the small intestine (for review see Szurszewski and Miller, 1994). Early studies demonstrated that these intestinointestinal reflexes persist after decentralisation of the prevertebral ganglia, although the threshold for activating the reflexes is increased by decentralisation (Kuntz and Saccomanno, 1944;Semba, 1954;Shapiro and Woodward, 1959). …”
Section: Indexing Terms: Prevertebral Ganglia; Enteric Nervous Systemmentioning
confidence: 99%
“…The reflexes can be elicited by distension of the colon and by distension or chemical stimuli applied intraluminally in the small intestine (for review see Szurszewski and Miller, 1994). Early studies demonstrated that these intestinointestinal reflexes persist after decentralisation of the prevertebral ganglia, although the threshold for activating the reflexes is increased by decentralisation (Kuntz and Saccomanno, 1944;Semba, 1954;Shapiro and Woodward, 1959). …”
Section: Indexing Terms: Prevertebral Ganglia; Enteric Nervous Systemmentioning
confidence: 99%
“…To ensure that our results were not an artifact resulting from the use of electrical stimulation we repeated the experiment using distension of the duodenum to evoke reflex relaxation. Inhibition of gastric contractions and decrease in intragastric pressure in response to distension of the upper small intestine (Schapiro & Woodward, 1959;Jansson & Martinson, 1966;Grundy & Scratcherd, 1982) is thought to be predominantly via splanchnic afferents and efferents, although there may be a splanchno-vagal component (Glise & Abrahamsson, 1980;Grundy & Scratcherd, 1982).…”
Section: Duodenal Inflation 8tudymentioning
confidence: 99%
“…In addition to conveying central preganglionic sympathetic output to abdominal viscera, these ganglia participate in peripheral reflexes between visceral organs (Lawson & Holt, 1937;Kuntz & Van Buskirk, 1941;Warkentin, Haston, Preston & Ivy, 1943: Kuntz & Saccomanno, 1944Brown & Pascoe, 1952;Semba, 1954;Schapiro & Woodward, 1959). Individual ganglion cells integrate peripheral afferent synaptic input from visceral mechanosensory fibres with synaptic input from central, preganglionic sympathetic nerve fibres (Crowcroft, Holman & Szurszewski, 1971;Kreulen & Szurszewski, 1979b;Szurszewski, 1981) to determine the output firing rate along postganglionic efferent pathways to the visceral end organs.…”
Section: Introductionmentioning
confidence: 99%